Neuroanthropology: evolution and emotional embodiment - Campbell, Benjamin C.; Garcia, Justin R. (Frontiers in Evolutionary Neuroscience, 2009)
The Decade of the Mind is a proposal for a research initiative focused on four areas of neuroscience, including mental health, high-level cognitive function, education, and computational applications. Organizing efforts to date have primarily included cognitive scientists, computer scientists, and engineers, as well as physicians. At the same time anthropologists have started to explore the implications of neuroscience for understanding culture. Here we suggest that evolutionary neuroscience can be used to bridge knowledge obtained by social scientists with that obtained in the neurosciences for a more complete appreciation of the mind. We consider such a perspective as neuroanthropology. We use embodiment, an anthropological concept that has been substantiated by recent findings in neuroscience, to illustrate an integrative biocultural approach within neuroanthropology and suggest future possible directions for research.